2019
DOI: 10.1186/s12906-019-2635-0
|View full text |Cite
|
Sign up to set email alerts
|

Withania somnifera (L.) Dunal ameliorates neurodegeneration and cognitive impairments associated with systemic inflammation

Abstract: Background Systemic inflammation driven neuroinflammation is an event which correlates with pathogenesis of several neurodegenerative diseases. Therefore, targeting peripheral and central inflammation simultaneously could be a promising approach for the management of these diseases. Nowadays, herbal medicines are emerging as potent therapeutics against various brain pathologies. Therefore, in this contemporary study, the neuroprotective activity of Ashwagandha ( Withania somnifera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 77 publications
1
22
0
Order By: Relevance
“…WS leaf aqueous extract ameliorated inflammatory cytokine-induced neuroinflammation by inhibiting the NF-κB pathway in the rat model ( Gupta and Kaur, 2018 ). The same extract also showed a neuroprotective effect by normalizing MAP2 expression in microglial cells ( Gupta and Kaur, 2019 ). Therefore, this extract can be a promising candidate to prevent neuroinflammation.…”
Section: Probable Role Of Withania Somnifera In Covid-19 Pathophysiologymentioning
confidence: 99%
“…WS leaf aqueous extract ameliorated inflammatory cytokine-induced neuroinflammation by inhibiting the NF-κB pathway in the rat model ( Gupta and Kaur, 2018 ). The same extract also showed a neuroprotective effect by normalizing MAP2 expression in microglial cells ( Gupta and Kaur, 2019 ). Therefore, this extract can be a promising candidate to prevent neuroinflammation.…”
Section: Probable Role Of Withania Somnifera In Covid-19 Pathophysiologymentioning
confidence: 99%
“…It was observed that after 8 weeks of administration, water extract of Ashawagandha ameliorated the inflammatory condition by suppressing the production of inflammatory cytokines viz. IL-1β, IL-6, and TNF-α by inhibiting Nuclear factor kappa B (NF-κB), P38 and mitogen activated protein kinase (MAPKs) signaling pathway [77,78]. WA treatment suppressed the activation of the nucleotide binding domain leucin rich repeat (NLRP3) inflammasome that further inhibited the IL-1β secretion in LPS induced macrophages and also suppressed the Helicobacter pylori stimulated production of IL-1β from dendritic cells by modulating NLRP-3 inflammasome and NF-κB activation in a dose dependent manner [79].…”
Section: Anti-inflammatory and Health Mediated Properties Of Withania Somniferamentioning
confidence: 99%
“…Ageing remains an unavoidable and complex natural occurrence that can lead to the emergence of neurodegenerative diseases. It has been linked with a reduction in cognitive function which can significantly affect the quality of life (Gupta & Kaur, 2019). The term 'Nutraceutical' was derived from 'nutrition' and 'pharmaceutics'.…”
Section: Introductionmentioning
confidence: 99%